Estudo do fator de dano acumulado (CDF) de pavimentos aeroportuários brasileiros utilizando FAARFIELD e BAKFAA – Avaliação da incorporação de geogrelhas - Santilli, Sérgio Ricardo (Universidade Federal de São Carlos, 2024)
Brazilian airport pavements, designed during an era of lower aircraft weights, now face up with challenges due to increased traffic and heavier aircraft, as well as aging infrastructure, predominantly constructed between the 1950s and 1970s. A way to evaluate the structural condition of pavements is by determining the Cumulative Damage Factor (CDF), which considers the mechanical characteristics of the existing structure and the aircraft operations. Therefore, this research involves collecting data on aircraft characteristics, traffic patterns, and pavement layer properties to update information on the pavement life service of existing Brazilian airfield pavements. The research involves data collection and analysis of the CDF of 20 Brazilian airport runways pavement. Backanalysis of deflection basins obtained from Heavy Weight Deflectometer (HWD) tests is conducted using the BAKFAA software. The FAARFIELD software is then employed to calculate the CDF, incorporating the latest information on aircraft mix and pavement conditions. Notably, 11 airports exhibit a CDF less than 0.01, suggesting potential oversizing of pavements for existing aircraft movement. Boa Vista Airport/RR (SBBV) stands out with a CDF of 1.5, prompting recommendations for actions to mitigate pavement degradation. In the second stage, the incorporation of geosynthetics in airport pavements was evaluated through computational numerical modeling with the Finite Element Method using ABAQUS. Parametric analyzes evaluated the effects of stabilization by geosynthetic reinforcement in different positions of the structure, verified by the decrease in CDF and reduction in deflections. Furthermore, the CDF was recalculated for this condition. The findings offer valuable insights for future actions, maintenance strategies, and recommendations for the construction of new airports.
Study of the cumulative damage factor (CDF) of Brazilian airport pavements using FAARFIELD and BAKFAA – Implications of the incorporation of geogrids
Keywords: Pavimento aeroportuário; Cumulative damage factor; Bakfaa; Faarfield; Geossintético; Airport pavement; Geosynthetic; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA; ENGENHARIAS::ENGENHARIA CIVIL